The Political Effect on Indonesia's Stock Market from "Peringatan Darurat" Demonstration” - Wicaksono, Rhenaldy Pius; Gunawan, Flavian Naretius; Suganda, Tarsisius Renald; Cahyadi, Rino Tam (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This study investigates the market reaction to the "Peringatan Darurat" demonstration in Indonesia, triggered by political unrest, focusing on its impact on the Indonesia Composite Index (IHSG) using the INFOBANK 15 index as the sample. Political demonstrations are external events that may influence investor behavior and market dynamics. The Infobank 15 index is selected for its representation of companies with large market capitalizations and high trading liquidity, primarily from the banking sector, which plays a central role in the economy. An event study approach is used to analyze abnormal returns and trading volume activity (TVA) as proxies for market reaction. Results show a significantly positive abnormal return during the event window, indicating that the market interpreted the demonstration as containing positive informational value. However, TVA during and after the event did not show significant differences, suggesting minimal impact on trading activity. These findings imply that the Indonesian capital market reacts to political events but perceives the "Peringatan Darurat" demonstration as a routine occurrence with limited long-term impact on market stability.